The head of state as a subject of counteraction to corruption: a comparative legal analysis - Plastun, Myhailo (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article is devoted to the study of the theoretical and practical features of the participation of the head of state in counteracting corruption. The experience of foreign countries in the constitutional and legal and sectoral regulation of the forms and methods of the influence of the head of state on the implementation of anti-corruption policy is analyzed. On the basis of this analysis, the anti-corruption functions of the head of state are systematized. It is noted that the use of positive foreign experience in counteracting corruption, with its appropriate adaptation to domestic realities, will contribute to increasing the effectiveness of combating this negative phenomenon, will significantly reduce the level of corruption in the state and will provide Ukraine with sustainable socio-economic development and a prosperous future.